Specifications of the ACMG/AMP variant interpretation guidelines for germline TP53 variants. Issue 3 (25th December 2020) - Fortuno, Cristina; Lee, Kristy; Olivier, Magali; Pesaran, Tina; Mai, Phuong L.; de Andrade, Kelvin C.; Attardi, Laura D.; Crowley, Stephanie; Evans, D. Gareth; Feng, Bing‐Jian; Foreman, Ann K. M.; Frone, Megan N.; et al.
Abstract: Germline pathogenic variants in TP53 are associated with Li‐Fraumeni syndrome, a cancer predisposition disorder inherited in an autosomal dominant pattern associated with a high risk of malignancy, including early‐onset breast cancers, sarcomas, adrenocortical carcinomas, and brain tumors. Intense cancer surveillance for individuals with TP53 germline pathogenic variants is associated with reduced cancer‐related mortality. Accurate and consistent classification of germline variants across clinical and research laboratories is important to ensure appropriate cancer surveillance recommendations. Here, we describe the work performed by the Clinical Genome Resource TP53 Variant Curation Expert Panel (ClinGen TP53 VCEP) focused on specifying the American College of Medical Genetics and Genomics and the Association for Molecular Pathology (ACMG/AMP) guidelines for germline variant classification to the TP53 gene. Specifications were developed for 20 ACMG/AMP criteria, while nine were deemed not applicable. The original strength level for the 10 criteria was also adjusted due to current evidence. Use of TP53 ‐specific guidelines and sharing of clinical data among experts and clinical laboratories led to a decrease in variants of uncertain significance from 28% to 12% compared with the original guidelines. The ClinGen TP53 VCEP recommends the use of these TP53 ‐specific ACMG/AMP guidelines as the standard strategy for TP53 germline variant classification. Abstract : Here, we detail the work of the ClinGen TP53 Variant Curation Expert Panel focused on adapting the ACMG/AMP variant curation guidelines to germline variants in TP53. The use of these guidelines and sharing of clinical data led to a reduction in the number of variants of uncertain significance. Moreover, the use of these guidelines is recommended as the standard strategy for TP53 variant classification.